Persistence and genetic adaptation of Pseudomonas aeruginosa in patients with chronic obstructive pulmonary disease. (July 2022) - Eklöf, Josefin; Misiakou, Maria A.; Sivapalan, Pradeesh; Armbruster, Karin; Browatzki, Andrea; Nielsen, Thyge L.; Lapperre, Therese S.; Andreassen, Helle F.; Janner, Julie; Ulrik, Charlotte S.; Gabrielaite, Migle; Johansen, Helle K.; et al.
Abstract: Objectives: It is unclear whether recurrent sputum culture with Pseudomonas aeruginosa from patients with chronic obstructive pulmonary disease (COPD) is caused by intermittent airway carriage by different P. aeruginosa lineages or persistent carriage by the same lineage, and whether lineages genetically adapt during carriage. Methods: Whole-genome sequencing was performed for P. aeruginosa isolates sampled longitudinally from sputum cultures in patients with COPD who were enrolled in an ongoing randomized controlled trial (clinicaltrials.gov: NCT03262142 ). Results: A total of 153 P. aeruginosa isolates were sequenced for 23 patients during 365 days of follow-up. Recurrent presence of P. aeruginosa was seen in 19 patients (83%) and was caused by persistence of the same clonal lineage in all but one patient. We identified 38 genes mutated in parallel in two or more lineages, suggesting positive selection for adaptive mutations. Mutational enrichment analysis revealed genes important in antibiotic resistance and chronic infections to be more frequently mutated. Discussion: Recurrent P. aeruginosa was common and carried for a prolonged time after initial detection in the airways of patients with COPD. Recurrence was caused by persistence of the same clonal lineage and was associated with genetic adaptation. Trial data on possible clinical benefits of attempting antibiotic eradication of P. aeruginosa in COPD are warranted.